Clinicopathological significance of the microRNA‐146a/WASP‐family verprolin‐homologous protein‐2 axis in gastric cancer. Issue 7 (10th June 2017) - Yao, Qunyan; Tu, Chuantao; Lu, Di; Zou, Yanting; Liu, Hongchun; Zhang, Shuncai
Abstract : Gastric cancer (GC) is one of the most common malignancies, and cancer invasion and metastasis are the leading causes of cancer‐induced death in GC patients. WASP‐family verprolin‐homologous protein‐2 (WASF2), with a role controlling actin polymerization which is critical in the formation of membrane protrusions involved in cell migration and invasion, has been reported to possess cancer‐promoting effects in several cancers. However, data of WASF2's role in GC are relatively few and even contradictory. In this study, we analyzed WASF2 expression in GC tissues and their corresponding adjacent normal tissues. We found that WASF2 was upregulated in GC tissues and high level of WASF2 was associated with lymph node metastasis of GC. Through gain‐ and loss‐of‐function studies, WASF2 was shown to significantly increase GC cells migration and invasion, but had no effect on proliferation in vitro . Importantly, WASF2 was also found to enhance GC metastasis in vivo . Our previous research suggested that WASF2 was a direct target of microRNA‐146a (miR‐146a). Furthermore, we analyzed miR‐146a's level in GC tissues and their corresponding adjacent normal tissues. We found that miR‐146a was downregulated in GC tissues and low miR‐146a level was associated with advanced TNM stage and lymph node metastasis. The level of WASF2 in GC tissues was negatively correlated with miR‐146a expression and had inverse clinicopathologic features. The newly identified miR‐146a/WASF2 axis may provide a novel therapeutic target for GC. Abstract : WASF2 was up‐regulated in GC tissues and high level of WASF2 was associated with lymph node metastasis of GC. Functional research demonstrated tha t WASF2 increased GC cells migration and invasion in vitro and enhanced GC metastasis in vivo . Further study suggested that WASF2 was regulated by miR‐146a in GC. And the miR‐146a/WASF2 axis has cardinal clinicopathological significance in GC patients.